Rácz, Ildikó Mária: A lét és a szerelem szentsége. Ivan Bunyin művészi világképe. L’Harmattan, Budapest 2020, 373 pp. ISBN 978-963-414-681-0 - Dukkon, Ágnes (Slavica, 2022)
This review presents a critical analysis of the monograph on Bunin by the Hungarian researcher Ildikó Mária Rácz. The author describes the main thematic blocs of the volume, for example, the influence of classic Russian literature on Bunin (Turgeniev, Tolstoi, Chekhov, and Tiutchev), the role of Eastern philosophy in the evolution of Bunin’s art, the connection between the modern psychological concepts (Freud, Jung) and the short stories as Mitya’s love or The grammar of love.